First search for atmospheric and extraterrestrial neutrino-induced cascades with the IceCube detector - Abbasi, R.; Abdou, Y.; Abu-Zayyad, T.; Adams, J.; Aguilar, J.; Ahlers, M.; Andeen, K.; Auffenberg, J.; Bai, X.; Baker, M.; Barwick, S.; Bay, R.; et al. (2011)
We report on the first search for atmospheric and for diffuse astrophysical neutrino-induced showers (cascades) in the IceCube detector using 257 days of data collected in the year 2007–2008 with 22 strings active. A total of 14 events with energies above 16 TeV remained after event selections in the diffuse analysis, with an expected total background contribution of 8.3±3.6. At 90% confidence we set an upper limit of E2Φ90%CL<3.6×10−7  GeV•cm−2•s−1•sr−1 on the diffuse flux of neutrinos of all flavors in the energy range between 24 TeV and 6.6 PeV assuming that Φ∝E−2 and the flavor composition of the νe:νμ:ντ flux is 1:1:1 at the Earth. The atmospheric neutrino analysis was optimized for lower energies. A total of 12 events were observed with energies above 5 TeV. The observed number of events is consistent with the expected background, within the uncertainties.